Totalitarianism : the inner history of the Cold War - Gleason, Abbott (Oxford Univ. Press, 1995)
Publisher description: Providing a fascinating account of totalitarianism, historian Abott Gleason offers a penetrating chronicle of the central concept of our era--an era shaped first by our conflict with fascism and then by our conflict with communism. Interweaving the story of intellectual debates with the international history of the twentieth century, Gleason traces the birth of the term to Italy in the first years of Mussolini's rule. He follows the growth and expansion of the concept as it was picked up in the West and applied to Hitler's Germany and the Soviet Union. Gleason's account takes us through the debates of the early postwar years, as academics adopted the term, notably Hannah Arendt. The concept fully entered the public consciousness with the opening of the Cold War, as Truman used the rhetoric of totalitarianism to sell the Truman Doctrine to Congress. As he takes his account through to the 1990s, Gleason offers an inner history of the Cold War, revealing the political charge the term carried for writers on both the left and the right. He also explores the intellectual struggles that swirled around the idea in France, Germany, Italy, Czechoslovakia, and Poland. When the Cold War drew to a close in the late 1980s, Gleason writes, the concept lost much of its importance in the West even as it flourished in Russia, where writers began to describe their own collapsing state as totalitarian